Post-Crisis Anglo-Saxon Capitalism - Christopher J. Nock; Catherine Coron (Revue LISA)
In France, the label “Anglo-Saxon capitalism” has tended to suggest an intimate link between the U.K. economic model and that of the United States of America. This link is thought to run much deeper than mere economics. It includes linguistic and cultural ties that distinguish a broad-based Anglo-Saxon socio-economic and political model from the French and other models. This paper first considers to what extent a distinctive Anglo-Saxon economic model can be identified. It then considers U.K. and U.S. responses to the 2008-2009 financial and economic crisis to determine if they are sufficiently similar to support ongoing reference to an Anglo-Saxon economic model. The final part considers the extent to which the pre-crisis Anglo-Saxon model contributed to the recent crisis of global capitalism, and whether Anglo-American capitalism has actually come out of the ruins.